Climate-based suitability assessment for alternate wetting and drying water management in the Philippines: a novel approach for mapping methane mitigation potential in rice production - Sander, Björn Ole; Wassmann, Reiner; Palao, Leo K.; Nelson, Andrew (Informa UK Limited, 2017)
The ‘alternate wetting and drying’ (AWD) technology for rice is a water-saving technology with a high greenhouse gas (GHG) mitigation potential. The Philippine government attempts to disseminate AWD in all national irrigation systems in order to adapt to increasingly scarce water resources.